2019
DOI: 10.17159/2413-3221/2019/v47n2a502
|View full text |Cite
|
Sign up to set email alerts
|

Perception And Adaptation Responses To Climate Change: An Assessment Of Smallholder Livestock Farmers In Amathole District Municipality, Eastern Cape Province

Abstract: Livestock is a critical asset for many rural poor, however, the current climate crisis is affecting livestock farmers. A cross-sectional household survey was conducted in order to assess the farmers' perceptions of climate change, and its impact on production and adaptation responses. Using a multistage sampling procedure, a total of 142 smallholder livestock farmers were selected from 18 villages across the study area. Descriptive and inferential statistical tools were used and the observed results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Research on climate change impacts on agricultural production activities in the study area revealed that smallholder farmers were faced with numerous production challenges caused by extreme weather events, particularly long periods of dry spells [165][166][167]. Amongst the identified impacts are water paucity, increased irregularities in planting seasons, pest and diseases, and decreased soil fertility affecting the quality and yields of crops [165].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on climate change impacts on agricultural production activities in the study area revealed that smallholder farmers were faced with numerous production challenges caused by extreme weather events, particularly long periods of dry spells [165][166][167]. Amongst the identified impacts are water paucity, increased irregularities in planting seasons, pest and diseases, and decreased soil fertility affecting the quality and yields of crops [165].…”
Section: Discussionmentioning
confidence: 99%
“…Amongst the identified impacts are water paucity, increased irregularities in planting seasons, pest and diseases, and decreased soil fertility affecting the quality and yields of crops [165]. Others include reduction in the weight, development, milk production and reproduction of livestock, coupled with reduction in vegetation and available land area for grazing [166]; and, marked decrease in the size, quantity and quality of poultry eggs [167]. Further assessment of the adaptation responses of smallholder farmers in the area showed that there was an extremely low implementation of adaptation measures and a majority of the farmers perceived existing coping and adaptation measures as significantly ineffective [165][166][167].…”
Section: Discussionmentioning
confidence: 99%
“…pastoralists resorted to destocking to acquire income for alternative livelihoods. Similar studies byPopoola et al (2019) in the Eastern Cape, South Africa, reported that 55% of respondents use destocking as an adaptation measure Popoola et al (2019). further noted that some pastoral communities cushion against drought through destocking.…”
mentioning
confidence: 59%
“…At the same time, the cost to farmers increased by 177% (Molieleng et al, 2021), making it very difficult as most of the farmers had to rely on buying feed to sustain their livestock production (Talanow et al, 2021). In most cases, such costs were done to maintain the core herd (Popoola et al, 2019). It has been anticipated that will take years to recover (Tibesigwa et al, 2017).…”
Section: Updating Literature Progress On Climatic Risks and Mitigatio...mentioning
confidence: 99%
“…Only a few have associated adaptations to specific climate change impacts [e.g., (Maponya and Mpandeli, 2012;Mthembu and Zwane, 2017)]. To develop effective adaptation strategies and ensure adaptation success, research on climate change adaptation must not be approached separately but should instead be integrated within the framework of impact assessments (Popoola et al, 2019;Oduniyi et al, 2020). The documented adaptation responses are mostly incremental through management and technology adjustments to reduce the impacts, and less on systemic measures such as institutional and policy changes.…”
Section: The Silo Approach To Investigate Climate Change Impacts On L...mentioning
confidence: 99%